Anthropology of sport in the Spanish university: current situation and prospects - Jordi-Sánchez, Mario (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
This text outlines some general guidelines about the situation of the anthropology of sport in Spanish universities. To this end, we carried out a detailed analysis of the undergraduate and postgraduate study plans currently offered in Spanish public and private universities. As main results, we highlight some general aspects that explain the current situation of the anthropological of sport and some of its main consequences. Finally, we point out the most substantial contributions that this discipline can make to a deep understanding of the sociocultural foundations of sport and raise some of the main prospects.